Ответ(ы) на вопрос:
[latex]515. 1)3 \frac{4}{15} -2 \frac{1}{8}- \frac{1}{24}= 3 \frac{4}{15} -2 \frac{3}{24}- \frac{1}{24} =3 \frac{4}{15}- 2\frac{2}{24}= [/latex] [latex]3 \frac{4}{15}- 2\frac{1}{12} = 3 \frac{4}{60}- 2\frac{5}{60}=2 \frac{64}{60}- 2\frac{5}{60}= \frac{59}{60}; [/latex]
[latex]2)-3- 2\frac{2}{3}-4 \frac{5}{6}+7 \frac{1}{2} = -3-2 \frac{4}{6}-4 \frac{5}{6}+7 \frac{3}{6}= [/latex] [latex]-3-2 \frac{4}{6}-4 \frac{5}{6}+7 \frac{3}{6}=-2 \frac{6}{6} -2 \frac{4}{6}-4 \frac{5}{6}+7 \frac{3}{6}=-8 \frac{15}{6}+7 \frac{3}{6} = [/latex] [latex]-(8 \frac{15}{6}-7 \frac{3}{6})=-1 \frac{12}{6} =-1 \frac{2}{1};[/latex] Ибо не знаю, что делать.
[latex]3)1 \frac{5}{6}-2 \frac{5}{9}+4 \frac{1}{3}-3 \frac{1}{2}=1 \frac{15}{18}-2 \frac{10}{18}+4 \frac{6}{18}-3 \frac{9}{18}= [/latex] [latex]- \frac{13}{18}+ \frac{15}{18}=+( \frac{15}{18}- \frac{13}{18})= \frac{2}{18}= \frac{1}{9}; [/latex]
[latex]4)0,25- \frac{7}{12}+0,5- \frac{1}{6}= \frac{1}{4}- \frac{7}{12}+ \frac{1}{2}- \frac{1}{6}= \frac{3-7+6-2}{12}= \frac{0}{12}=0; [/latex]
[latex]516)1)3,9a-2,81b-5,1a+4,9b=2,09b-1,2a;[/latex]
[latex]2)1 \frac{3}{4}x-3 \frac{7}{11}y+2 \frac{1}{4}x-5 \frac{4}{11}y=1,75x+2,25x-3 \frac{7}{11}-5 \frac{4}{11}=4x-9y; [/latex]
[latex]3)-1 \frac{5}{12}m- \frac{5}{7}n- \frac{7}{12}m- \frac{2}{7}n=-1 \frac{5}{12}m- \frac{7}{12}m- \frac{5}{7}n- \frac{2}{7}n=-2m-n; [/latex]
Не нашли ответ?
Похожие вопросы